برنامج مقترح في التربية الوقائية لتنمية المعارف والسلوكيات الوقائية اللازمة لمواجهة فيروس كورونا COVID-19 لدى أطفال الروضة - محمد، ماجدة فتحي سليم; محمد، هناء محمد عثمان Othman, Hana Mohammed (جامعة الإسكندرية - كلية رياض الأطفال, 2021)
هدف البحث الحالي إلى تعرف أثر برنامج مقترح في التربية الوقائية لتنمية المعارف والسلوكيات الوقائية اللازمة لمواجهة فيروس كورونا "COVID-19". وتكونت عينة البحث من مجموعتين (ضابطة وتجريبية)، قوام كل مجموعة (31) طفلا وطفلة؛ ولتحقيق هدف البحث قامت الباحثتان بإعداد؛ قائمة بالمعارف المتعلقة بفيروس كورونا، وقائمة بالسلوكيات الوقائية، واختبار تحصيلي، ومقياس السلوكيات الوقائية، وبرنامج مقترح في التربية الوقائية. وقد قامت الباحثتان بإجراء التكافؤ بين المجموعتين. وأظهرت نتائج البحث من خلال مقارنة أداء أطفال مجموعتي البحث في التطبيق البعدي لأداتي القياس أن هناك فروقا ذات دلالة إحصائية لصالح أطفال المجموعة التجريبية، وهذا يدل على الأثر الإيجابي للبرنامج المقترح على تنمية المعارف والسلوكيات الوقائية لدى أطفال مجموعة البحث التجريبية. وقد ثبت ذلك من خلال حساب حجم الأثر باستخدام مربع إيتا Eta squared (η²) الذي جاء مساويا (0.93) في بطاقة الاختبار التحصيلي، وجاء مساويا (0.96) في مقياس السلوكيات الوقائية. وفي ضوء هذه النتائج أوصى البحث بمجموعة من التوصيات كان منها: ضرورة تضمين مناهج رياض الأطفال المفاهيم والموضوعات المرتبطة بالتربية الوقائية اللازمة لمواجهة الأوبئة والأمراض المعدية مثل فيروس كورونا المستجد.
The current research aims to know the impact of a proposed program on preventive education to develop knowledge and preventive behaviors necessary to confront the Coronavirus "COVID- 19". The research sample consisted of two groups (control and experimental), each group consisted of (31) children. To achieve the goal of the research, the two researchers prepared: A list of knowledge related to Coronavirus, a list of preventive behaviors, an achievement test, a measure of preventive behaviors, and a proposed program in preventive education. The two researchers conducted parity between the two groups. The results of the research, by comparing the performance of the children of the two research groups in the post application of the two measurement tools, showed that there are statistically significant differences in favor of the children of the experimental group, and this indicates the positive effect of the proposed program on developing knowledge and preventive behaviors among children of the experimental research group. This was proven by calculating the size of the effect using the Eta squared (²η), which was equal to (0.93) in the achievement test card, and was equal to (0.96) on the preventive behaviors scale. In light of these results, the research recommended a set of recommendations, including: The necessity to include in kindergarten curricula the concepts and topics related to preventive education necessary to confront epidemics and infectious diseases
Keywords: رياض الأطفال -- التربية الوقائية -- فيروس كورونا -- التوعية الصحية -- أطفال الروضة